TECHNOLOGY OF OBTAINING FUNCTIONAL PRODUCTS ON THE BASIS OF PROCESSING OF OIL FLAX SEEDS - Тараймович, Ирина (SWorldJournal, 2021)
In the article the main directions of linseed oil in Ukraine and especially in Polissya, analyzed feasibility of growing flax oil in Western Polissya in the context of the current conditions of economic operation Ukraine proposed a comprehensive seed proc